Physique, anaerobic power and pulmonary measures of Botswana track athletes - Onyewadume, I. U.; Amusa, L. O.; Owolabi, E. O. (Kinesiology, 2004)
This study profiled the physique (anthropometry, body composition and somatotypes), leg power and pulmonary measures of Botswana track athletes gathered in a sports camp for the All Africa Games held in Johannesburg, South Africa. The intention was to provide coaches and trainers with the necessary data that enabled them to adjust their training programmes to improve the performance parameters in which shortfalls were noticed. The sample of participants comprised thirteen (13) male athletes, who competed in the sprinting and relay events at the All Africa Games. Their mean age was 24.3 ± 2.8 years. The components of physique assessed included stature, body mass, body fat percentage, body mass index and somatotype ratings of endomorphy, mesomorphy and ectomorphy. Anaerobic power measurements included peak, minimum and average power (W) and power drop (W/s). The pulmonary functions test included vital capacity (VC), forced expiratory volume (FEV1), FEV1percentage, maximum expiratory flow (PEF), forced vital capacity (FVC) and forced expiratory flow (FEF) at 25, 50 and 75% of FVC. Data were analysed using descriptive statistics. The results for physique revealed a mean body mass value of 65.3 ± 9.2 kg, mean stature of 174.2 ± 8.1 cm, mean body density (BD) value of 1.08643 ± 3.9 gm/cc, a mean body fat percentage value of 5.6 ± 1.6%, a mean body mass index value of 21.5 ± 2.7 kg.m-2and mean somatotype value of 1.36 ± 0.6, 3.81 ± 1.4 and 3.21 ± 1.3 for endomorphy, mesomorphy and ectomorphy, respectively, indicating that the athletes were ectomorphic-mesomorphs. The athletes` mean leg power outputs were 651.75 ± 1.4W, 313.68 ± 1.06W, 486.84 ± 1.34W, -1.92 ± 0.6W/s for peak power, minimum power, average power and power drop, respectively. The athletes` mean pulmonary measures were 3.2 ± 0.67, 1.92 ± 0.78, 59.12 ± 1.2 and 3.07 ± 0.93 for VC, FEV1, FEV1% and FVC, respectively. It was concluded that the physique values were typical of similar athletes involved in sprint events. However, the athletes` pulmonary and peak leg power outputs were very low compared to values from athletes in similar events, hence requiring training adjustments.